The extended monod model for microalgae growth and nutrient uptake in different wastewaters - Mohd Sadiq, Ummal Aisha Farhana; En, Yow Meow; Jamaian, Siti Suhana (Science Publishing Corporation, 2018)
Water pollution is a serious issue which always being concerned by public. Microalgae for wastewater treatment is an effective way to solve the problem due to its eco-friendly and apparently low cost. This research aims to investigate the efficiency of the mathematical model to estimate the microalgae growth and nutrient uptake by microalgae in wastewaters. The extended Monod model is applied in the Verhulst model to describe the microalgae growth and nutrient uptake by microalgae whereas microalgae Botryococcus sp. is the species of microalgae used in this research. The microalgae Botryococcus sp. growth and nutrient uptake in domestic, agricultural and industrial wastewater are estimated and the results reveal that the extended Monod model is suitable for the estimation of microalgae growth and nutrient uptake by microalgae. In addition, microalgae Botryococcus sp. is promising for treating domestic, agricultural and industrial wastewater.